2020
DOI: 10.1186/s12887-020-02036-6
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary behavior patterns and adiposity in children: a study based on compositional data analysis

Abstract: Background: Between-person differences in sedentary patterns should be considered to understand the role of sedentary behavior (SB) in the development of childhood obesity. This study took a novel approach based on compositional data analysis to examine associations between SB patterns and adiposity and investigate differences in adiposity associated with time reallocation between time spent in sedentary bouts of different duration and physical activity. Methods: An analysis of cross-sectional data was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 49 publications
6
50
1
4
Order By: Relevance
“…Our findings are in accordance with previously published studies reporting that meeting the ST recommendation is associated with lower odds of obesity whether or not PA and sleep recommendations are met [22,39]. It can be assumed that ST, a main contributor to the total SB, accumulates with a few prolonged uninterrupted sedentary periods, which are associated with excess adiposity independently of PA [40].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in accordance with previously published studies reporting that meeting the ST recommendation is associated with lower odds of obesity whether or not PA and sleep recommendations are met [22,39]. It can be assumed that ST, a main contributor to the total SB, accumulates with a few prolonged uninterrupted sedentary periods, which are associated with excess adiposity independently of PA [40].…”
Section: Discussionsupporting
confidence: 92%
“…Ortega and colleagues [ 55 ] found that morning tiredness is associated with lower odds of participating in leisure-time PA and higher odds of excessive screen time, which is in line with our findings. This SB pattern has been associated with increased risk of several adverse health outcomes among children and adolescents, such as adiposity [ 65 ] and cardiometabolic markers [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of the authors' knowledge, no research has used compositional data analyses to examine bout durations across the activity spectrum, including both SED and PA bouts, to assess associations with a range of cardiometabolic outcomes. One study by Gába and colleagues [11] used a similar approach, yet only investigated SED bout durations alongside total volumes of other intensities, and associations with adiposity. Their results suggested bene ts to adiposity from replacing middle bouts (de ned as 10-29 min) with shorter SED bouts (1-9 min), yet found no associations for replacements with long bouts (≥ 30 min duration) [11].…”
Section: Discussionmentioning
confidence: 99%
“…One study by Gába and colleagues [11] used a similar approach, yet only investigated SED bout durations alongside total volumes of other intensities, and associations with adiposity. Their results suggested bene ts to adiposity from replacing middle bouts (de ned as 10-29 min) with shorter SED bouts (1-9 min), yet found no associations for replacements with long bouts (≥ 30 min duration) [11]. This contrasts with the present study that did not nd bene ts of engaging in a particular (shorter or longer) type of SED bouts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation